Interethnic tolerance development ways among pedagogical students at University - Soldatchenko, Aleksandr L. (2021)
The presented article is devoted to interethnic tolerance development among pedagogical students at a university.Based on the works by B. Barber, J. Berry, A.G. Asmolov, M.S. Mirimanov, V.A. Lektorsky, G.U. Soldatov and other researchers, the authors clarified the goal and objectives of interethnic tolerance development among future teachers, and also systematized its main criteria and indicators. Also, the article presents the author's complex of pedagogical conditions that ensure the development of interethnic tolerance among pedagogical students at a university. The complex includes the following components: the use of active didactic forms and interactive teaching methods in the educational process that contribute to the formation of a tolerant worldview of students; organization of interpersonal interaction of pedagogical students by their inclusion in research activities; actualization of tolerant interethnic communication experience among future teachers through the introduction of tolerance episodes into the educational process; the development of competence among pedagogical students in the field of interethnic tolerance development among schoolchildren during the educational process.